" GRANDMOTHER" AND ITS SUPPLEMENTARY OPPOSITES (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
This article is devoted to learn lexical units of kindship, especially “grandmother”. Also, comparative analysis of significant differences among its supplementary opposites are reflected, particular points to consider about meaning of “grandmother” as a lexeme in discourse matters are listed in this paper.